Multiomics analysis of kernel development in response to short-term heat stress at the grain formation stage in waxy maize - Guo, Jian (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.